Phenolic compounds, functional and antioxidant properties of flours from microwave pre-treated Bambara groundnut seeds - Duodu, Kwaku Gyebi (University of Pretoria, 2024)
Dissertation (MSc (Food Science))--University of Pretoria, 2019.